2021
DOI: 10.1029/2021gl095476
|View full text |Cite
|
Sign up to set email alerts
|

Short Periodic VLF Emissions Observed Simultaneously by Van Allen Probes and on the Ground

Abstract: Very low frequency (VLF) emissions in the magnetosphere are often observed in the form of periodic or quasiperiodic sequence of bursts. Helliwell (1965) termed periodic emissions (PE) as the bursts having repetition periods of 3-10 s consistent with individual wave packet propagation between conjugate ionospheres. This period can be very stable in time for long time intervals. Quasi-periodic (QP) emissions have longer periods (usually from 20-30 to 300 s), and the inter-element interval can vary smoothly due t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…This pattern resembles the bouncing‐element event reported by Demekhov et al. (2021), and some, probably nonlinear, mechanism seems necessary to compensate for the group velocity dispersion. Such a mechanism has been suggested by Bespalov (1984) and recalled by Bespalov et al.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This pattern resembles the bouncing‐element event reported by Demekhov et al. (2021), and some, probably nonlinear, mechanism seems necessary to compensate for the group velocity dispersion. Such a mechanism has been suggested by Bespalov (1984) and recalled by Bespalov et al.…”
Section: Discussionsupporting
confidence: 86%
“…Surprisingly, this bouncing is not accompanied by dispersion, as one might expect for whistler-mode waves. This pattern resembles the bouncing-element event reported by Demekhov et al (2021), and some, probably nonlinear, mechanism seems necessary to compensate for the group velocity dispersion. Such a mechanism has been suggested by Bespalov (1984) and recalled by Bespalov et al (2010), see also Trakhtengerts and Rycroft (2008).…”
Section: Discussionsupporting
confidence: 81%
“…A powerful tool for the wave propagation analysis is a comparison of simultaneous measurements, best provided by a ground‐based station and a spacecraft. In such a case, it is possible to study both the temporal and spatial evolution of the waves (e.g., Martinez‐Calderon, Němec, et al., 2020; Titova et al., 2015) and to obtain important pieces of information about the wave propagation (Demekhov et al., 2021; Martinez‐Calderon et al., 2016). Moreover, statistical studies of such wave events can provide an overall picture of the favorable conditions for the wave occurrence and penetration through the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, statistical studies of such wave events can provide an overall picture of the favorable conditions for the wave occurrence and penetration through the ionosphere. However, it is challenging to obtain a sufficiently large data set to perform such a statistical analysis, and hence only case studies are often reported (e.g., Demekhov et al., 2017, 2021; Martinez‐Calderon, Katoh, et al., 2020; Němec et al., 2016). These case studies focus on a concrete kind of whistler mode waves, quasiperiodic emissions (Carson et al., 1965; Sato & Kokubun, 1980), and a detailed analysis of available multipoint observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation